ANALISIS ABC DAN VEN TERHADAP BELANJA OBAT DI RSUD DR. SOEDARSO PONTIANAK TAHUN 2010 - , Erlin Nofriana, Dr. Sri Suryawati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: RSUD dr. Soedarso is a hospital owned by Provincial Government of West Borneo. The pharmacy installation of RSUD dr. Soedarso is responsible in conducting pharmacy service comprising planning, procurement, distribution and the usage. The drug planning is conducted based on the average consumption per month and three months. There are many prescription sheets that are not served since there is no needed drug available. The drug expense should be suitable with the drug necessity for the disease dealt with. In order to know the preciseness, it is used two kinds of evaluation instrument, including ABC analysis to view the drug that consumes large expense and VEN. Purpose: Conducting analysis on the drug expense in 2010 is by ABC analysis and VEN in order to assist RSUD dr. Soedarso to improve the better planning of drug necessity. Method: The research uses case study design with analytic descriptive approach. The analysis is started by collecting the data of drug expense and drug price list in each depot at IFRS dr. Soedarso starting from January until December 2010. Thus, the data of drug expense in a year is classified based on active substance, later on, the cumulative percentage is counted and conducted ABC analysis. The result of ABC value, then, is analyzed further by considering VEN criteria. Moreover, since the hospital has not had medication standard yet, so the VEN criteria is based on DOEN in 2008. Result: 1) The drug expense process of RSUD dr. Soedarso uses consumption method conducted by apothecary in every depot and approved by Head of IFRS. Therefore, the team of drug special planning has not been formed. Formularies have not been revised for ages. The hospital has not had medication standard. 2) The result of ABC analysis shows that the A category is 30 drug items, B category is 60 drug items and C category is 257 drug items. The drug including V criteria is 9 drug items, E criteria is 153 drug items and N criteria is 185 drug items. Apparently, the A category is dominated by 13 drug items including in N criteria, by absorbing the cost of drug expense is 1,86 billion IDR. Conclusion: 1) The drug expense process of RSUD dr. Soedarso uses consumption method done by apothecary in every depot and approved by head of IFRS. RSUD dr. Soedarso has not formed team of integrated drug special planning consisting of related parties as well as involving the member of hospital KFT. 2) The 2010 drug expense has not effective and efficient yet since it is more than half of non-essential drug item and absorbs more than 39,6% of drug expense.